The Renaissance Roots of the Digital Turn - Piotr (Comunicación, 2016)
In the following article I trace affinities between Renaissance ideas and the digital turn in contemporary humanities. There is a need to define this turn by referring to important historical achievements of quadro and cinquecento: the concept of mathesis universalis, its holistic understanding of theory and practice, symbiosis of art, technê, and science, interest in human anatomy, designing media and communications. By invoking them I address several problems: how the humanities should be dealing with digital technologies, how humanists should work, and what are the consequences of biomediations.